Tydeus shabestariensis sp. nov. and description of the male of Neopronematus sepasgosariani (Acari: Tydeoidea), with a key to the Iranian species of Tydeus - Akbari, Ali; Irani-Nejad, Karim Haddad; Khanjani, Mohammad; Arzanlou, Mahdi; Kaźmierski, Andrzej (Zootaxa, 2015)
A new species of the family Tydeidae from Iran, Tydeus shabestariensis sp. nov., is described from adult males and females collected from soil in apple orchards. A key to species of Tydeus of Iran, based on females, is provided. The male of Neopronematus sepasgosariani (Tydeoidea: Iolinidae) is also described and illustrated for the first time.